The effect of social media on customer purchase decisions in the beverages industry in Zimbabwe. - Mbetu, Judith (Midlands State University, 2020)
The researcher was motivated into conducting this research study by the need to know and understand the effects of social media on customer purchase decisions. The objectives of the study were to establish the influence of digital consumer interaction on need recognition, to investigate the effect of electronic word of mouth on information search, to investigate the effect of product attributes on evaluation of alternatives and to assess the extent to which brand online communities can enhance purchase decisions and post purchase behaviour. The researcher adopted a quantitative methodology and used a case study design. The researcher constructed questionnaires and administered them to a sample of 380 respondents. The collected data was analysed through SPSS version 16. The findings of the data were presented in tables. The researcher tested the reliability of the data using Cronbach‟s Alpha. The researcher used descriptive statistics to describe social media and customer purchase decisions. Multiple regression analysis was performed to determine the impact of social media on customer purchase decisions. The probability values were also used to test the hypotheses. The researcher found out that there is a positive impact of digital consumer interaction on need recognition, there is a positive relationship between electronic word of mouth on information search, there is a positive impact of product attributes on evaluation of alternatives and also that there is a positive relationship between brand online communities and customer purchase decisions. The researcher concluded that social media has a positive and significant effect on customer purchase decisions. The researcher recommended that beverage companies should use social media since it has a positive and significant influence on customer purchase decisions. The sample size used by the researcher was relatively small and the researcher could not generalise the findings to the whole beverage industry. The researcher proposed that future studies should replicate the same and employ large sample size to enhance generalisation of findings.